PENERAPAN BAHAN AJAR GEOMETRI RUANG BERBANTUAN GEOGEBRA PADA MATERI IRISAN BIDANG PADA BANGUN RUANG - Destia Wahyu Hidayati; Lenny Kurniati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
ne of subject material which is learned by students in Mathematics Education Program is 3D-Shapes Geometry. The average of 3D-Shapes Geomery students’s mark in IKIP Veteran Jawa Tengah is still under 70. The average of 3D-Shapes Geometry student’s mark is low because their critical thinking ability is low too. It is caused by learning material which is used. This teaching aid just consists of material and exercise. Students also too depend on confirmation from their lecturer to give decision of the truth answer when they were doing the exercise inthe learning material. The solution of this problem is they can use 3D-Shapes Geometry Learning using Geogebra because they can check the truth answer by Geogebra. There are steps that students do when they were using Geogebra. This research is quantitative research. Instrument of this research is critical thinking ability test. This research use One Sample T-Test and gain. The conclusion of this research are the average of 3D-Shapes geometry’s mark is more than 70 and the increase of average 3D-Shapes Geometry’s mark is in the middle category. Keywords: Learning material, 3D-shapes geometry, geogebra, critical thinking ability